253 Determining the Relationship Between Different Risk Factors with Pelvic Organ Prolapse Incidence in Sows. (12th April 2022) - Waltrich, Andre; Rodrigues, João Victor Facchini; Filho, Rosiel Cavalcante; Siqueira, Amanda P; Lisboa, Pedro G; da Silva, Gefferson Almedia; Vaz, Gilberto Carlos; Silva, Rodrigo; Vier, Carine M; Lu, Ning; Cast, Wayne R; Dritz, Steve; et al.
Abstract: Our objective was to evaluate the relationship of different putative factors with the occurrence of pelvic organ prolapse (POP) in sows. Data from 1, 028 sows (PIC Landrace or PIC Camborough, Hendersonville TN) was collected at the final third of gestation, pre-farrowing, at farrowing, and post-farrowing from July to September 2021 in 2 sow farms located in South of Brazil. The annualized prolapse incidence from the 2 farms in 2021 was 2.22 and 3.63%. Whole-herd information and individual sow measurements were collected, including prolapse incidence, farrowing assistance, performance records, tail length, body condition score measured by caliper, perineal score (PS), fecal score (FS), oxytocin use. A logistic regression model using PROC LOGISTIC in SAS (Cary, NC) was utilized to assess risk factors associated with POP incidence rate, with sow as the experimental unit. Sows with PS3 and PS2 had greater ( P < 0.001) POP incidence compared with sows with PS1 (38.46, 9.41, and 0.96%, respectively). Thin sows had greater ( P < 0.001) POP incidence compared with ideal and fat sows combined (5.8 and 1.76%, respectively). Thin sows with FS1 (dry feces) had greater ( P = 0.04) POP incidence compared with thin sows with FS2 and FS3 (normal feces; 8.09% and 1.81%, respectively), but no evidence for differences were observed for fat and ideal sows. Sows receiving farrowing assistance had higher (P <0.001) POP incidence compared with sows that were not sleeved (13.16 and 2.41%, respectively). Sows with tail length <13cm had greater ( P = 0.01) POP incidence compared with sows with tail length >13cm (5.18 and 2.25%, respectively). There was also no evidence for an association between use of oxytocin ( P = 0.38), total pigs born ( P = 0.38), or total litter weight ( P = 0.53) and POP incidence. In summary, PS, body condition, FS, farrowing assistance, and tail length appeared to be contributing factors associated with POP incidence in this system.